Implementing a group singing intervention for postpartum depression within the Italian health service - Lega, Ilaria; Luzi, Ilaria; Mastroeni, Simona; Ferraro, Claudia; Andreozzi, Silvia; Donati, Serena; Grussu, Pietro; Cavazzana, Valentina; Proietti, Patrizia; Magliocchetti, Patrizia; Monaldi, Chiara; Biglia, Cristina; et al. (Frontiers in Medicine, 2024)
Background: In the United Kingdom a singing intervention for Postpartum Depression (PPD) titled "Music and Motherhood" was found to be effective. The World Health Organization Regional Office for Europe coordinated a study to assess the feasibility of implementing and adapting the intervention in other countries. In Italy, recent studies have highlighted the need to promote the availability of effective interventions for PPD in primary care.Aim: To describe the implementation of "Music and Motherhood" within the Italian primary care services dedicated to pregnancy and postnatal care in three different geographical locations, thus providing an example of strategies for implementing an arts and health intervention in primary care that can improve health and well-being.Methods: A 10-week group singing intervention for mothers with PPD was conducted as part of a single arm feasibility study. Data were collected through one-to-one interviews, focus groups and questionnaires from the professionals involved in the implementation and selected participating mothers. A conceptual framework including acceptability, appropriateness, feasibility, fidelity, implementation process, costs and sustainability was adopted for analysis. Number of sessions attended by mothers and implementation outcome measures for acceptability, appropriateness and feasibility, each consisting of four items rated on a 5-point Likert scale were also gathered.Results: The intervention was found to be inclusive of women from different socio-cultural backgrounds and appropriate to the context. The group setting and the use of an arts-based intervention helped to de-medicalise the process of care maximising resources. Singing helped mothers to express their feelings and find strategies to improve interaction with their child. Attention to mothers' needs and the co-presence of the professional singing leader and a health professional were among the key factors. The median number of sessions attended was nine out of ten. In terms of acceptability, almost 90% of the professionals were in complete agreement that they liked and approved the intervention.Conclusion: Our study adds to the evidence that an arts and health intervention proven effective in one culture and linguistic context can be adapted to another. Collaboration among health professionals and artists in the implementation process and adequate funding are instrumental in moving from project to programme level.